2020
DOI: 10.1093/jas/skaa311
|View full text |Cite
|
Sign up to set email alerts
|

Dietary taurine supplementation attenuates lipopolysaccharide-induced inflammatory responses and oxidative stress of broiler chickens at an early age

Abstract: This study was conducted to investigate the effect of taurine as a prophylactic treatment on antioxidant function and inflammatory responses of broilers challenged with lipopolysaccharide (LPS). A total of 256 one-day-old male Arbor Acres broiler chicks were randomly assigned to 4 treatments with 8 replicates of 8 birds (8 birds/cage). Four treatment groups were designated as follows: 1) in the CON group, broilers fed a basal diet; 2) in the LPS group, LPS-challenged broilers fed a basal diet; 3) in the LPS + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 81 publications
3
24
2
Order By: Relevance
“…As the essential adrenocortical hormone in chickens, the CORT has been widely used as a critical indicator to measure the degree of stress in broilers ( Curtis et al, 1980 ). However, in the present study, its increase at 8 and 24 h was not statistically significant, which was inconsistent with some previous results ( Han et al, 2020 ; Zheng et al, 2020 ). In those studies ( Han et al, 2020 ; Zheng et al, 2020 ), taurine and pyrroloquinoline quinone disodium were supplemented to broiler feed to reduce the inflammatory responses caused by LPS.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As the essential adrenocortical hormone in chickens, the CORT has been widely used as a critical indicator to measure the degree of stress in broilers ( Curtis et al, 1980 ). However, in the present study, its increase at 8 and 24 h was not statistically significant, which was inconsistent with some previous results ( Han et al, 2020 ; Zheng et al, 2020 ). In those studies ( Han et al, 2020 ; Zheng et al, 2020 ), taurine and pyrroloquinoline quinone disodium were supplemented to broiler feed to reduce the inflammatory responses caused by LPS.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in the present study, its increase at 8 and 24 h was not statistically significant, which was inconsistent with some previous results ( Han et al, 2020 ; Zheng et al, 2020 ). In those studies ( Han et al, 2020 ; Zheng et al, 2020 ), taurine and pyrroloquinoline quinone disodium were supplemented to broiler feed to reduce the inflammatory responses caused by LPS. Compared with taurine and pyrroloquinoline quinone disodium, danofloxacin might have a stronger ability to alleviate the secretion of these proinflammatory cytokines in chickens.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, the minimum dosage of LPS showing negative effects on the poultry was uncertain. Some studies on broilers found that LPS over 0.5 mg/kg could trigger the declines in the growth, immune and oxidative stresses, along with the damages in the intestines ( Csernus et al., 2020 ; Han et al., 2020 ; Chen and Yu, 2021 ). However, few studies were available associated with the dosage effects of LPS on ducks.…”
Section: Discussionmentioning
confidence: 99%
“…Several AAs (e.g., Arg, glutamic acid, glycine, Pro, and leucine) participate in cell signal transmission and metabolic regulation ( Wu et al, 2014 ). The Tau, a sulfated compound synthesized by the eukaryotic host, could increase the ADG and hepatic antioxidant status, while relieve lipopolysaccharide-induced inflammation of broiler chickens ( Han et al, 2020 ). A constant supply of sufficient AAs to living cells from the blood is required to ensure protein accretion in the skeletal muscle of growing pigs ( Regmi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%